Mitigating Readers’ Doubts: The Use of Exemplification in Students’ Academic Writing (Pascasarjana Universitas Negeri Makassar, 2022)
This study explores the use of Exemplification in undergraduate students’ academic writing at a university in Lesotho. Research indicates that Exemplification is a prevalent feature of academic writing. However, it has also been established that learners experience difficulties in forming and using Exemplification effectively. Using a corpus created from research projects written by final year undergraduate students in six faculties at a university in Lesotho, the study examined the use of Exemplification, focusing on the exemplification markers students used, the patterns of exemplification as well as the errors in using exemplification effectively. Findings indicate that students used a limited set of exemplification markers and only a few patterns. It was also observed that students had challenges using exemplification appropriately. The study concludes that there is a need for explicit teaching of Exemplification in EAP classes.